Pulmonary lesions associated with intratracheal Benzo(a)pyrene instillation in Sprague Dawley rats - Mustapha, Mazlina; Karim, Abdulkarim Jafar; Saad, Mohd Zamri; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2011)
This study was conducted to assess acute exposure to very low dose of intratracheally instilled Benzo(a)pyrene (BaP) on the lungs of rats. A total of 30 rats were utilized in this study and they were randomly divided into 6 groups. The control group (G1) did not receive any treatment, whereas the rats in the remaining 5 groups were administered with 13.8 ng of BaP, which were then sacrificed at 1 hour (G2), 8 hours (G3), 16 hours (G4), 32 hours (G5), and 72 hours (G6) of post-instillation (p.i.). Morphological appearances of all the lungs of all the treated rats consisted of various degrees of congestion, mostly evident in G3 and early development of emphysema, as seen in G4. These worsened as time progressed as observed in G6. On the other hand, the histological findings of the lungs of the treated rats revealed that the lungs had underwent some changes that were characterized by progressive alveolar congestion, epithelialisation with emphysema and accompanied by infiltration of inflammatory cells predominantly with alveolar macrophages and some neutrophils. However, even with such lesions seen, there was no apparent manifestation of impairment of the pulmonary system.